Decreasing patient cost and travel time through pediatric rheumatology telemedicine visits. Issue 1 (December 2016) - Kessler, Elizabeth; Sherman, Ashley; Becker, Mara
Abstract Background There is a critical shortage of pediatric rheumatologists in the US. Substantial travel to clinics can impose time and monetary burdens on families. The aim of this study was to evaluate the cost of in-person pediatric rheumatology visits for families and determine if telemedicine clinics resulted in time and cost savings. Factors associated with interest in telemedicine were also explored. Methods Surveys were offered to parents and guardians of patients in Pediatric Rheumatology follow-up clinics in Kansas City, Missouri, the primary site of in-person care, and at a telemedicine outreach site 160 miles away, in Joplin, Missouri. Survey questions were asked about non-medical, out-of-pocket costs associated with the appointment and interest in a telemedicine clinic. Results At the primary Kansas City clinic, the median distance traveled one-way was 40 miles [IQR = 18–80]. In the Joplin sample, the median distance traveled to the telemedicine clinic was 60 miles [IQR = 20–85] compared to 175 miles [IQR = 160–200] for the same cohort of patients when seen in Kansas City (p < 0.001). When the Joplin cohort was seen via telemedicine they missed less time from work and school (p = 0.028, p = 0.003, respectively) and a smaller percentage spent money on food compared to when they had traveled to Kansas City (p < 0.001). There was no statistical difference between the Joplin cohort when they had traveled to Kansas City and the Kansas City cohort in terms of miles driven to clinic, time missed from work and school, and percentage of subjects who spent money on food. Conclusions Traditional in-person visits can result in a financial toll on families, which can be ameliorated by the use of telemedicine. Telemedicine leveled the economic burden of clinic visits so that when the Joplin cohort was seen via telemedicine, they experienced costs similar to the Kansas City cohort.